Effect of in-season neuromuscular and proprioceptive training on postural stability in male youth basketball players - Ondra, L.; Nátesta, P.; Bizovska, L.; Kubonová, E.; Svoboda, Z. (Acta Gymnica, 2017)
Background: Poor balance ability is a predictor of injuries of the lower extremity. Multi-intervention proprioception preventive programs, comprising balance training, strength, plyometric, agility, running, and stretching exercises, are effective in improving balance ability and reducing the risk of lower extremity injuries in athletes.